1997
DOI: 10.1007/s004310050629
|View full text |Cite
|
Sign up to set email alerts
|

A review of teicoplanin in the treatment of serious neonatal infections

Abstract: Teicoplanin (8-10 mg/kg) administered intravenously or intramuscularly once daily after a loading-dose regimen of 15-20 mg/kg per day appears to be an effective and well tolerated treatment for Gram-positive infections in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
0
26
1
Order By: Relevance
“…The lack of ion suppression is crucial in an LC-MS/MS method, as suppression has been shown to compromise detection selectivity. 32 A calibration curve spanning the therapeutic range of Teicoplanin samples at four concentrations (20,50, 100 and 200 mg/mL) were evaluated for their intra-assay (n ¼ 10) and inter-assay (n ¼ 20) imprecision 25-75 mg/mL was demonstrated to be linear up to 200 mg/mL, and can be consistently reproduced having an r 2 value .0.99. These preliminary steps to ensure both teicoplanin and ristocetin can be reliably measured by LC-MS/MS are of paramount importance so the performance characteristics of the method are suitable and reliable for the intended analytical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of ion suppression is crucial in an LC-MS/MS method, as suppression has been shown to compromise detection selectivity. 32 A calibration curve spanning the therapeutic range of Teicoplanin samples at four concentrations (20,50, 100 and 200 mg/mL) were evaluated for their intra-assay (n ¼ 10) and inter-assay (n ¼ 20) imprecision 25-75 mg/mL was demonstrated to be linear up to 200 mg/mL, and can be consistently reproduced having an r 2 value .0.99. These preliminary steps to ensure both teicoplanin and ristocetin can be reliably measured by LC-MS/MS are of paramount importance so the performance characteristics of the method are suitable and reliable for the intended analytical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Imprecision of the method was assessed by the analysis of four QC samples at various concentrations (20,50, 100 200 mg/mL). These samples were analysed 10 times each within a single run to determine intra-assay imprecision, and also analysed in separate batches (n ¼ 20) over a fourweek period to assess inter-assay imprecision.…”
Section: Imprecisionmentioning
confidence: 99%
“…Teicoplanin is used as alternative therapy to vancomycin only in Europe [26,27]. However, some studies have shown an increase in the isolation of CNS with reduced susceptibility to teicoplanin worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 We used this dosage in our patients with high bacteriological cure rates. In a review of non-comparative studies by Fanos et al, 4 the clinical efficacy and bacteriological cure rates were found to be as high as 100%.…”
Section: Discussionmentioning
confidence: 99%
“…1 -3 Several causative organisms of neonatal sepsis have been isolated over the years; currently, Staphylococcus aureus and coagulase-negative staphylococci (CoNS) represent the most frequently isolated nosocomial pathogens from neonates in the NICU. 4,5 These organisms show significant resistance to methicillin and/or aminoglycosides, which may be as high as 70 -90%, thus glycopeptide antibiotics are used in many NICUs. 2,5 -8 Vancomycin is a glycopeptide antibiotic that has been used in nurseries for many years, despite its side-effects.…”
Section: Introductionmentioning
confidence: 99%